Accuracy between virtual surgical planning and actual outcomes in orthognathic surgery by iterative closest point algorithm and color maps: A retrospective cohort study - Marlière, D-A-A; Demétrio, M-S; Schmitt, A-R-M; Lovisi, C-B; Asprino, L; Chaves-Netto, H-D-M (Medicina oral, patología oral y cirugía bucal, 2019)
To evaluate the accuracy between actual outcomes and virtual surgical planning (VSP) in orthognathic surgery regarding the use of three-dimensional (3D) surface models for registration using iterative closest point (ICP) algorithm and generated color maps. Construction of planning and postoperative 3D models in STL files format (M0 and M1, respectively) from CBCT of 25 subjects who had been submitted to bimaxillary orthognathic surgery was performed. M0 and M1 were sent to Geomagic software in semi-automatic alignment surface mesh order of M0 and M1 for registration using ICP algorithm to calculate mean deviation (MD, MD+, MD-, SD) and root mean square (RMS - 3D Error). Color maps were generated to assess qualitative congruence between M0 and M1. From deviation analysis, 3D Error was defined as accuracy measurement. To assess the reproducibility, the workflow was performed by two evaluators multiple times. t-tests were used to assess whether all means of MD, MD+, MD-, SD and 3D Error values would be ≤ - 2 mm and ≥ 2 mm. High intra and inter evaluators correlation were found, supporting the reproducibility of the workflow. t-tests proved that all MDs and 3D Error values were > - 2 mm and < 2 mm. 3D error mean was within the standards of clinical success lower than 2 mm. ICP algorithm provided a reproducible method of alignment between 3D models and generated color maps to evaluate 3D congruence but did not answer all methodological parameters regarding the assessment of accuracy in orthognathic surgery.